Al-Ash’ara is the closest sect to the Sunnis and Hadith - Ibrahim, Nuri Abd El-Rahman (Journal of Islamic Sciences, 2019)
This research is entitled (Ashaira closest sects to the Sunnis and the Hadith) , lies the importance of this research in that it shows that the Ashari doctrine in the final outcome as the closest communities to the Sunnis and Hadith, the result of the research and investigation, which bothers Abul Hassan al - Ash’ari through Its new approach and its victory for the views of the Sunnis and the community, derived from the sources of sources adopted by the Sunni scholars, and standing hard gilded by the attacks that attempted to undermine the qualities of the Creator and other doctrinal issues , It is among the scandals of the Mu’tazilah and contradicting their words and their corruption unless he is shown by others; because he was one of them and he had studied Ali Abu al-Jaba’i for forty years. He was wise and then returned from them. He was classed in the response to them , And then moved to the method of the son of kallab, which is closer to the year of the method of Mu’tazilah; it proves the attributes and the higher and the difference of God to the creatures and makes the higher proves the mind; and the experience of the Ash’ari Almzatlp revealed the contradiction and corruption. And the evidence of the contradiction between the Mu’tazilah, the Shiites, the philosophers and others has become of his sanctity and fate has become him, and the installers of the qualities of them proves the qualities known to the hearing as evidenced by the qualities known to the mind, and this is the words of the people of the Sunnah private Ahl al-Hadith and agreed, Evidence, including Abu al-Hasan al-Ash’ari. Therefore, the poet is considered the closest denomination to the Sunnis and Hadith.